2021
DOI: 10.1021/acsnano.1c01077
|View full text |Cite
|
Sign up to set email alerts
|

Interfacially Engineered ZnxMn1–xS@Polydopamine Hollow Nanospheres for Glutathione Depleting Photothermally Enhanced Chemodynamic Therapy

Abstract: Fenton-like reactions driven by manganese-based nanostructures have been widely applied in cancer treatment owing to the intrinsic physiochemical properties of these nanostructures and their improved sensitivity to the tumor microenvironment. In this work, Zn x Mn 1−x S@polydopamine composites incorporating alloyed Zn x Mn 1−x S and polydopamine (PDA) were constructed, in which the Fenton-like reactions driven by Mn ions can be tuned by a controllable release of Mn ions in vitro and in vivo. As a result, the Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(88 citation statements)
references
References 58 publications
1
87
0
Order By: Relevance
“…Such strategies can be roughly outlined into TME modulation, usage of external stimuli, utilization of chemical and biological stimuli, and design of the nanoplatforms (Table 1). [ 16,17,22,34–36,40,43–105 ]…”
Section: Strategies To Enhance Chemodynamic Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Such strategies can be roughly outlined into TME modulation, usage of external stimuli, utilization of chemical and biological stimuli, and design of the nanoplatforms (Table 1). [ 16,17,22,34–36,40,43–105 ]…”
Section: Strategies To Enhance Chemodynamic Therapymentioning
confidence: 99%
“…AFeNPs@CAI CDT MDA-MB-231 [35] FePt@FeOx@TAM-PEG CDT 4T1 [43] UCNP@PVP@MIL88B CDT U87MG [44] H 2 O 2 generation PTCG (EGCG, Pt-OH, PEG-b-PPOH) CDT/Chemotherapy HepG2 [17] Copper hexacyanoferrate CDT 4T1 [40] Den-DOX-Fe 3+ -TA CDT/Chemotherapy U14 [45] PGC-DOX (PEG-GOx, CaCuP, DOX) CDT/Chemotherapy 4T1 [46] ACC@DOX•Fe 2+ -CaSi-PAMAM-FA/mPEG CDT/Chemotherapy A375, 4T1 [47] (MSNs@CaO 2 -ICG)@LA CDT/PDT MCF-7 [48] PZIF67-AT CDT 4T1 [49] Copper peroxide nanodots CDT U87MG [50] GSH depletion FA-Pyrite CDT CT26 [34] MMDM (microphage, MCN, DOX, MnO 2 ) CDT/Chemotherapy 4T1 [51] A@P/uLDHs (artemisinin, PEG, MgFe-LDH) CDT HeLa [52] CCMZ (Cu, CuMoO x , ZP) CDT 4T1 [53] JNP Ve (Au-MnO JNPs, IR1061) CDT/Radiotherapy MCF-7 [54] DMON@Fe 0 /AT CDT 4T1 [55] CMBP (CuO/MnO x @BSA, Pt(IV) prodrug) CDT/Chemotherapy 4T1 [56] Zn x Mn 1−x S/PDA CDT/PTT 4T1 [57] PtCu 3 nanocage CDT/SDT 4T1 [58] External stimuli Light DGU:Fe/Dox CDT/Chemotherapy 4T1 [59] LET-6 (tPy-Cy-Fe, DSPE-PEG) CDT/PTT U87MG [60] GNR@SiO 2 @MnO 2 CDT/PTT U87MG [61] SnFe 2 O 4 nanozyme CDT/PTT/PDT 4T1 [62] MoSe 2 /CoSe 2 @PEG CDT/PTT H-22 [63] HULK (liposome, laccase, MOHQ, FeCe6) CDT 4T1 [64] Cu-OCNP/Lap CDT/PTT HeLa [65] AuPd@Fe x O y CDT/PTT A549 [66] Fe-doped MoO x nanowires CDT/PTT HeLa [67] Hollow magnetite nanoclusters CDT/PTT HeLa [68] ICG@Mn/Cu/Zn-MOF@MnO 2 CDT/PTT/PDT U87 [69] Wesselsite (SrCuSi 4 O 10 ) nanosheets CDT/PTT/Starvation therapy 4T1 [70] MoP 2 nanorods CDT/PTT CAL27 [71] X-ray Cu 2 (OH)PO 4 @PAAS CDT/Radiotherapy HeLa [72] CoFe 2 O 4 nanoparticles CDT/Radiotherapy MCF-7…”
Section: Tme Modulation Ph Modulationmentioning
confidence: 99%
“…In recent years, the photothermal effect has been proved as an effective strategy to improve the treatment effect of CDT. [ 11 ] A variety of Fenton agents with good photothermal conversion performances have been explored, such as FeS 2 nanocubes, [ 12 ] Zn x Mn 1−x S@Polydopamine hollow nanospheres [ 13 ] and so on, [ 14 ] which triggered by the near‐infrared light in the first biowindow (NIR‐I, 750–1000 nm). Compared with NIR‐I lights, the NIR lights in the second biowindow (NIR‐II, 1000–1700 nm) have been aroused wide interest due to their intrinsic advantages of deeper tissue penetration and higher maximum permission exposure (MPE, 1.0 W cm −2 for 1064 nm).…”
Section: Introductionmentioning
confidence: 99%
“…Photothermal therapy (PTT) based on nanomaterials is another effective but less invasive therapeutic alternative, which converts near-infrared (NIR) light into local heat to realize tumor ablation. The hyperthermia generated in PTT can not only kill cancer cells but also speed up the Fenton-like reaction in CDT, consequently achieving a synergistic therapeutic outcome [ 8 , 10 , 11 ]. It has been reported that by constructing Au@semiconductor core-shell dual plasmonic hybrid nanocomposite, the photothermal conversion efficiency of nanocomposite could be efficiently improved because the core-shell structure could couple the localized surface plasmon resonance (LSPR) of two components to a maximum degree [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%